A role of frontal association cortex in long-term object recognition memory of objects with complex features in rats - Masmudi-Martín, Mariam; López-Aranda, Manuel Francisco; Navarro-Lobato, Irene; Khan, Zafaruddin (Federation of European Neuroscience Societies, 2024)
Perirhinal cortex is a brain area that has been considered crucial for the object recognition memory (ORM). However, with the use of an ORM enhancer named RGS14414 as gain-in-function tool, we show here that frontal association cortex and not the Perirhinal cortex is essential for the ORM of objects with complex features that consisted of detailed drawing on the object surface (complex ORM). An expression of RGS14414, in rat brain frontal association cortex, induced the formation of long-term complex ORM, whereas the expression of the same memory enhancer in Perirhinal cortex failed to produce this effect. Instead, RGS14414 expression in Perirhinal cortex caused the formation of ORM of objects with simple features that consisted of the shape of object (simple ORM). Further, a selective elimination of frontal association cortex neurons by treatment with an immunotoxin Ox7-SAP completely abrogated the formation of complex ORM. Thus, our results suggest that frontal association cortex plays a key role in processing of a high-order recognition memory information in brain.
Keywords: Complex features; Episodic memory; Frontal association cortex; Object memory behaviour; Object recognition; Pperirhinal cortex; Recognition memory; Simple features